Exploring the Potential of Agriculture in the Western Balkans : A Regional Report - World Bank Group (World Bank, Washington, DC, 2019)
This report aligns to the framework of structural transformation to identify opportunities for development in the agriculture sector in the Western Balkans, while also exploring patterns of trade and factors for improving agricultural competitiveness in the region. To build a pathway to modernization and to accelerate the agricultural transformation in the Western Balkans, the linkages between production, access to markets and trade flows need to be better understood. Focused strategies and interventions can improve the competitiveness of the agri-food sector, with wide-ranging impacts on food and nutrition security, export revenues and, ultimately, on domestic jobs and economic growth. The report provides a regional perspective on the challenges and opportunities for the sector. It builds on information from a variety of sources and own analytical work to address these knowledge gaps and support the dialogue on the transformation of agriculture into a modern and competitive sector in the region. To the extent possible, depending on data availability, country-specific inferences are also provided to guide country-specific directions for improving the productivity and competitiveness of the sector. The report explores the structural dynamics of the sector rather than EU pre-accession options. There is a wealth of information on the challenges and opportunities for agriculture in the context of EU pre-accession, both in terms of instruments and measures, as well as in terms of policy and resources. The value added of this report is the focus on structural dynamics, productivity patterns and their drivers, as well as multiplier effects and determinants of agricultural competitiveness in the region. These are explored from the perspective of pathways for change to accelerate the structural transformation of the sector and increase its competitiveness.